RELATIVE PERFORMANCE OF RICE-POTATO-GREEN GRAM SYSTEM IN RED AND LATERITIC ZONE OF WEST BENGAL UNDER ORGANIC, INORGANIC AND INTEGRATED NUTRIENT MANAGEMENT - CHATTERJEE, SOUROV; B. R. SIT,; P. K. SAHA,; GHOSH, DEBJANI; DEBNATH, ABHIJIT (The Bioscan, 2014)
An experiment was carried out during rabi and summer seasons from 2006 to 2009 in the dry sub-humid red and lateritic zone of West Bengal to study the effect of inorganic fertilizers alone or in combination with organic manures (FYM) on crop yield, nutrient uptake and soil properties under rice-potato-green gram cropping sequence. The experiment was laid out in split plot design with three sources of nutrients in main plot and three levels of nutrients in sub plots with three replications. Pooled data revealed that integrated sources of nutrients (combination of inorganic and organic sources) applied @125% recommended doses (RD) increased the yield of rice by 32.5%, potato by 81.5% and green gram by 47.3%, over the inorganic source applied @ 75% RD, under common practice. The maximum uptake of N, P and K by rice (114, 19 and 67.5 kg ha-1, respectively), potato (174, 18 and 187 kg ha-1, respectively) and green gram (78, 14.8 and 35 kg ha-1, respectively) was observed at 125% RD applied through integrated source. Pooled data over three years showed that conjoint use of chemical fertilizers and FYM has significantly improved the soil organic carbon by 17.07%, and available N, P, K and moisture content by 12.9%, 10.3%, 8.89% and 7.82%, respectively, over the inorganic fertilizer alone. It can be summarized that in this red and lateritic zone NPK should be applied at 125% of RD for each crop; half of this through inorganic fertilizer and the rest amount through FYM for increasing the productivity of the cropping sequence and sustaining the soil fertility.